Influence of engineering on the optimization of the performance of heavy machinery in Bagua 2022 - Ascona García, Papa Pio (2023)
The main problems of heavy machinery are inoperability, poor theoretical calculation of production, poor use of technologies for economic production and incomplete training, which negatively affect the optimization and performance of heavy machinery in Bagua 2022. In this sense, the objective of this research was to compare the influence of four dimensions: operability, theoretical calculation, economic production and training (independent variable X) with the performance variable (dependent variable Y). The methodology comprises the scientific method, inductive, non-experimental design, applied type, correlative level, quantitative approach, the population was 200 public servants, random probabilistic sampling, data collection was from INEI, and through surveys validated by experts. The statistical analysis was performed through descriptive statistics to generate simple graphs. The results indicate that there is a negative correlation between Operativity and Performance, Economic Production-Technology and Performance. Engineering and the comparison of dimensions such as calculation, production, and training have a significant influence on the optimal performance of heavy machinery, while operability does not have a significant influence.